Rare earths complexes of single arm N-aryl Schiff base ligand - Abid, Khalil Khalaf; Al-Barody, Sadeem Mohammad; Ahmad, Haslina (Scientia Research Library, 2014)
A synthesized ligand N – ( 2 – hydroxyphenyl) – 4 – n – butylsalicylaldimine (H2L) was used to prepare a series of mononuclear lanthanide complexes of the type [LnH2L(HL)2Cl] (Ln =LaIII, CeIII, SmIII and GdIII). The ligand and complexes were characterized by 1H, 13CNMR, elemental analysis (CHNO), FT-IR spectroscopy, GC-mass, Magnetic susceptibility Molar Conductivity and Thermo gravimetric analysis (TGA). Investigation of complexes suggest that two ligand molecules behaves as tridentate and the third one as bidentate as it present in zwitter ionic form with an additional one chloride ion to complete nine coordination geometry.